2022
DOI: 10.31234/osf.io/y9sfd
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Holistic and mechanical combination in psychological assessment: Why algorithms are underutilized and what is needed to increase their use

Abstract: Although mechanical combination results in more valid judgments and decisions than holistic combination, existing publications suggest that mechanical combination is rarely used in practice. Yet, these publications are either descriptions of anecdotal experiences or outdated surveys. Therefore, in several Western countries, we conducted two surveys (total N = 323) and two focus groups to investigate (1) how decision makers in psychological and HR practice combine information, (2) why they do (not) use mechanic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…For example, organizational psychologists may use standardized tests and interviews to hire new managers, and admissions officers may use grades and personal statements to admit students. In these situations, decision makers typically integrate information based on their expert judgment (Neumann, Niessen, Hurks, & Meijer, 2022;Vrieze & Grove, 2009), but they also sometimes receive algorithmic advice in the form of a performance prediction. An exemplary algorithm's prediction may be an unweighted sum score of a test score and an interview rating.…”
Section: Predicting Decision-makers' Algorithm Use 4 Predicting Decis...mentioning
confidence: 99%
“…For example, organizational psychologists may use standardized tests and interviews to hire new managers, and admissions officers may use grades and personal statements to admit students. In these situations, decision makers typically integrate information based on their expert judgment (Neumann, Niessen, Hurks, & Meijer, 2022;Vrieze & Grove, 2009), but they also sometimes receive algorithmic advice in the form of a performance prediction. An exemplary algorithm's prediction may be an unweighted sum score of a test score and an interview rating.…”
Section: Predicting Decision-makers' Algorithm Use 4 Predicting Decis...mentioning
confidence: 99%
“…Decision makers are algorithm averse, partly because they worry about negative stakeholder evaluations (Neumann, Niessen, Hurks, & Meijer, 2022;Nolan et al, 2016). Therefore, we investigated when stakeholders appreciate decision-makers' algorithm use more, and when decision makers worry less about negative stakeholder evaluations when using algorithms in hiring decisions.…”
Section: Discussionmentioning
confidence: 99%
“…An exemplary algorithm would be to add up a test score and an interview rating, and to hire the candidate(s) with the highest score(s). In practice, decision makers typically combine information holistically (Highhouse, 2008 One important reason why decision makers are algorithm averse is the "threat of technological unemployment" (TOTU, Meehl, 1986 p. 374): Decision makers worry that they provide less value to their organization when using algorithms because the hiring process and outcome is not attributed to their holistic judgment anymore (Burton et al, 2020;Neumann, Niessen, Hurks, & Meijer, 2022;Nolan et al, 2016Nolan et al, , 2020. Specifically, Nolan et al (2016) showed that decision makers are worried that stakeholders (e.g., colleagues, management, and applicants) give them less credit for their hiring decisions (i.e., perceive them as less responsible for and less in control of hiring decisions) when using algorithms rather than their holistic judgment.…”
Section: Introductionmentioning
confidence: 99%